Air pollution-induced placental epigenetic alterations in early life: a candidate miRNA approach. Issue 2 (1st February 2018) - Tsamou, Maria; Vrijens, Karen; Madhloum, Narjes; Lefebvre, Wouter; Vanpoucke, Charlotte; Nawrot, Tim S
ABSTRACT: Particulate matter (PM) exposure during in utero life may entail adverse health outcomes in later-life. Air pollution's adverse effects are known to alter gene expression profiles, which can be regulated by microRNAs (miRNAs). We investigate the potential influence of air pollution exposure in prenatal life on placental miRNA expression. Within the framework of the ENVIR ON AGE birth cohort, we measured the expression of six candidate miRNAs in placental tissue from 210 mother-newborn pairs by qRT-PCR. Trimester-specific PM2.5 exposure levels were estimated for each mother's home address using a spatiotemporal model. Multiple regression models were used to study miRNA expression and in utero exposure to PM2.5 over various time windows during pregnancy. The placental expression of miR-21 (−33.7%, 95% CI: −53.2 to −6.2, P = 0.022), miR-146a (−30.9%, 95% CI: −48.0 to −8.1, P = 0.012) and miR-222 (−25.4%, 95% CI: −43.0 to −2.4, P = 0.034) was inversely associated with PM2.5 exposure during the 2nd trimester of pregnancy, while placental expression of miR-20a and miR-21 was positively associated with 1st trimester exposure. Tumor suppressor phosphatase and tensin homolog (PTEN) was identified as a common target of the miRNAs significantly associated with PM exposure. Placental PTEN expression was strongly and positively associated (+59.6% per 5 µg/m³ increment, 95% CI: 26.9 to 100.7, P < 0.0001) with 3rd trimester PM2.5 exposure. Further research is required to establish the role these early miRNA and mRNA expression changes might play in PM-induced health effects. We provide molecular evidence showing that in utero PM2.5 exposure affects miRNAs expression as well as its downstream target PTEN .